The Visual Culture of Tolerance in Three Baliâ€™s Artworks of Balinese Artist: Putu Sutawijaya, 1998-2010 - Albar, Muhammad Wasith (Universitas Pendidikan Indonesia, 2020)
ABSTRACT: The contemporary life in the era of globalization marked by the fast forward of the tremendous IT (Information Technology). The information discharge excessively needs to have filter to separate the information visually and verbally. This paper studies the culture of tolerance in Balinese artist Putu Sutawijaya, on his three creations, to showed how the spirituality of Hinduâ€™s religion promulgate and develop the tolerance figure of his idea as form, which is an assertive spiritual attitude in the name of tolerance in plurality. Every society from a country, including Indonesia, must have a variety of differences, both culture, religion, race, value system, customs, habits, and history. While the spirituality was defined in descriptive analysis, historical anthropologist, and using the Wilhem Dilthey (2010)â€™s Hermeneutics Theory. The study of cultural tolerance in Putu Sutawijaya case can be found in his three contemporary works: â€œFire Sleep for a Momentâ€ in 1998; â€œIn Betweenâ€ in 2000; and â€œSolidarityâ€ in 2004. The novelty of this research is an effort to show how the Indonesiaâ€™s visual culture has a culture and religion tolerance as its main topics.KEY WORD: Visual Culture; Tolerance; Contemporary Artworks; Putu Sutawijaya.Â ABSTRAKSI: â€œBudaya Visual tentang Toleransi dalam Tiga Karya Seni Seniman Bali: Putu Sutawijaya, 1998-2010â€. Kehidupan kontemporer di era globalisasi ditandai dengan pesatnya kemajuan IT (Informasi Teknologi). Pembuangan informasi secara berlebihan perlu adanya filter untuk memisahkan informasi secara visual dan verbal. Makalah ini mengkaji budaya toleransi dari seniman Bali Putu Sutawijaya, pada tiga karyanya, untuk menunjukkan bagaimana spiritualitas agama Hindu menyebarluaskan dan mengembangkan sosok toleransi dari gagasannya sebagai wujud, yaitu sikap spiritual yang tegas atas nama toleransi dalam pluralitas. Setiap masyarakat dari suatu negara, termasuk Indonesia, pasti memiliki perbedaan yang beragam, baik budaya, agama, ras, sistem nilai, adat-istiadat, kebiasaan, dan sejarah. Manakala, spiritualitas didefinisikan dalam analisis deskriptif, antropologi sejarah, dan menggunakan Teori Hermeneutika dari Wilhem Dilthey (2010). Kajian tentang toleransi budaya dalam kasus Putu Sutawijaya dapat ditemukan dalam tiga karya seni kontemporernya: â€œFire Sleep for a Momentâ€ [Matikan Api Sejenak] pada tahun 1998; â€œIn Betweenâ€ [Diantara] pada tahun 2000; dan â€œSolidarityâ€ [Solidaritas] pada tahun 2004. Kebaruan penelitian ini merupakan upaya untuk menunjukkan bagaimana budaya visual Indonesia memiliki budaya dan toleransi beragama sebagai topik utamanya.KATA KUNCI: Budaya Visual; Toleransi; Karya Seni Kontemporer; Putu Sutawijaya.About the Author: Muhammad Wasith Albar, M.Hum. is a Lecturer of Art History at the Department of History, Faculty of Humanities UI (University of Indonesia), Depok UI Campus, Depok 16424, West Java, Indonesia. For academic interests, the Author is able to be contacted via e-mail address at: muhammadwasithalbar2000@gmail.comSuggested Citation: Albar, Muhammad Wasith. (2020). â€œThe Visual Culture of Tolerance in Three Baliâ€™s Artworks of Balinese Artist: Putu Sutawijaya, 1998-2010â€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 5(2), September, pp.143-160. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (July 17, 2020); Revised (August 17, 2020); and Published (September 30, 2020).